2021
DOI: 10.1136/tsaco-2020-000626
|View full text |Cite
|
Sign up to set email alerts
|

Complication to consider: delayed traumatic hemothorax in older adults

Abstract: BackgroundEmerging evidence suggests older adults may experience subtle hemothoraces that progress over several days. Delayed progression and delayed development of traumatic hemothorax (dHTX) have not been well characterized. We hypothesized dHTX would be infrequent but associated with factors that may aid prediction.MethodsWe retrospectively reviewed adults aged ≥50 years diagnosed with dHTX after rib fractures at two level 1 trauma centers (March 2018 to September 2019). dHTX was defined as HTX discovered ≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
(5 reference statements)
0
3
0
1
Order By: Relevance
“…This, coupled with the absence of any recent chest infection and apyrexia at the time of presentation, led the clinicians to reach the diagnosis of a likely delayed traumatic hemothorax. Delayed development of trauma-related hemothorax is rare but has been reported in the literature [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…This, coupled with the absence of any recent chest infection and apyrexia at the time of presentation, led the clinicians to reach the diagnosis of a likely delayed traumatic hemothorax. Delayed development of trauma-related hemothorax is rare but has been reported in the literature [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Menger et al, in 2012, identified the severity of chest injury classified by the AIS as the only independent factor related to post drainage complications 23 . There are studies that report a greater chance of late and after discharge rebleeding in approximately 1.4% of patients with chest injuries 24 , 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The study cohort comprised index hospitalization encounters of nonelderly adults (aged 18-64 years) hospitalized with a principal diagnosis of traumatic injury and any diagnosis of multiple rib fractures (International Classification of Diseases, Tenth Revision [ICD-10], diagnostic code, S22.4). We excluded elderly adults based on our hypothesis that their readmission etiologies are more likely to be confounded by baseline health conditions or associated with disparate etiologies (e.g., delayed hemothoraces 11,12 ). To mitigate confounding the association with our outcome (all-cause 3-month readmissions), we included patients with isolated major thoracic injuries (Abbreviated Injury Scale ≥3 of chest and <3 of other body regions).…”
Section: Study Cohortmentioning
confidence: 99%
“…The study cohort comprised 20,260 patients with rib fractures, among whom 11% (n = 2,185) experienced 3-month readmissions. Compared with patients who did not experience 3-month readmissions, patients who experienced 3-month readmissions were older (mean [SD] age, 51 [11] years vs. 48 [12] years) and had a lower proportion discharged to home after index hospitalization (78% vs. 91%; Table 1). Supplementary Figure 1, http://links.lww.com/TA/C703, displays the study cohort flow diagram, and Supplementary Table 3, http://links.…”
Section: Study Cohortmentioning
confidence: 99%